Enhanced meta-analysis and replication studies identify five new psoriasis susceptibility loci - Tsoi, Lam C.; Spain, Sarah L.; Ellinghaus, Eva; Stuart, Philip E.; Capon, Francesca; Knight, Jo; Tejasvi, Trilokraj; Kang, Hyun M.; Allen, Michael H.; Lambert, Sylviane; Stoll, Stefan W.; Weidinger, Stephan; et al. (Nature Communications, 2015)
Psoriasis is a chronic autoimmune disease with complex genetic architecture. Previous genome-wide association studies (GWAS) and a recent meta-analysis using Immunochip data have uncovered 36 susceptibility loci. Here, we extend our previous meta-analysis of European ancestry by refined genotype calling and imputation and by the addition of 5,033 cases and 5,707 controls. The combined analysis, consisting of over 15,000 cases and 27,000 controls, identifies five new psoriasis susceptibility loci at genome-wide significance (P<5 × 10(-8)). The newly identified signals include two that reside in intergenic regions (1q31.1 and 5p13.1) and three residing near PLCL2 (3p24.3), NFKBIZ (3q12.3) and CAMK2G (10q22.2). We further demonstrate that NFKBIZ is a TRAF3IP2-dependent target of IL-17 signalling in human skin keratinocytes, thereby functionally linking two strong candidate genes. These results further integrate the genetics and immunology of psoriasis, suggesting new avenues for functional analysis and improved therapies.
EVALuna2:9272